Mechanical properties and reasonable proportioning of similar materials in physical model test of tunnel lining cracking. (20th September 2021) - Xu, Zilong; Luo, Yanbin; Chen, Jianxun; Su, Zhongming; Zhu, Tantan; Yuan, Jiangpeng
Highlights: Through a series of proportional tests, the mechanical parameters of similar material of surrounding rock are stable, the range of variation is moderate, and the fabrication is convenient. Adding quartz sand to gypsum material can significantly improve the elastic modulus of material without reducing the compressive strength. When this similar material is applied to the model test, the mechanical and physical properties meet the test requirements. Abstract: Similar materials of surrounding rock and lining suitable for crack of tunnel lining are developed through numerous matching tests according to the numerous theory of geomechanical model test to study the mechanism of crack damage of long-span tunnel lining and the variation rules, such as load and deformation, of physical fields. Similar material of surrounding rock is composed of quartz sand as coarse aggregate, barite powder as fine aggregate, and oil, vaseline, and paraffin as binder. Similar material of lining is based on gypsum and quartz sand, diatomite, fly ash, barite powder, and cement as additives. Physical and mechanical parameters such as uniaxial compressive strength, elastic modulus, and cohesion of materials are controlled through uniaxial compressive, direct shear, and splitting tests. The influence laws of mechanical parameters under various ratios are systematically studied. Test results show that the mechanical parameters of similar material of surrounding rock made of quartz sand, barite powder, and vaseline are stable. The range of variation is moderate, and the fabrication is convenient. The adjustment range of physical and mechanical parameters of similar materials in surrounding rocks is 30.1–52.2 MPa of elastic modulus, 0.23–0.33 MPa of uniaxial compressive strength and 2147–2396 kg/m 3 of gravity. In the range of 1.2–2 water paste ratio, gypsum mixture is linearly weakened, and various admixtures strongly influence the mechanical properties of similar materials. Quartz sand as admixture can better replace aggregate in concrete. When the sand content is less than 20%, adding quartz sand into gypsum material can significantly improve the elastic modulus of the material, and the compressive strength changes minimally. When the sand content is more than 20%, the elastic modulus is basically unchanged and the compressive strength gradually decreases. When this similar material is applied to the model test of Fucunchuan tunnel lining crack in the Huangyan Road Capacity Expansion Project, the mechanical and physical properties meet the test requirements. The material can effectively simulate the development and evolution of cracks, provide material basis for obtaining good test results, and serve as a reference for the selection of similar materials for a similar model test.